Dialektizmi v Prežihovi zbirki Samorastniki - Zorko, Zinka (Jezik in slovstvo, 1993)
One of the most evident characteristics of Prežih's Samorastniki are dialectisms. The writer incorporated into his masterful and picturesque narratives individual dialectal words, sayings, folk wisdoms and set phrases, which we know from his own dialect of Kotlje. With them he enriched the Slovene literary language and expanded the limits of our knowledge and scope with a new and living folk tradition.
Keywords: Prežihov Voranc, 1893-1950; slovenska proza; narečja; dialect; dialectology; dialektologija; literarne študije; Prežihov Voranc: Samorastniki